186. A Systematic Literature Review on the Economic Burden of Illness in Gonorrhea. (31st December 2020) - Martin, Amber; Mitrani-Gold, Fanny S; Turner, Monica; Schiller, Emma; Joshi, Ashish V
Abstract: Background: In 2016, the World Health Organization estimated the global incidence of gonorrhea (GC) to be 86.9 million, and the reported incidence of GC in 2017 was 145.8 cases per 100, 000 females and 212.8 cases per 100, 000 males in the US. GC therefore represents a significant global healthcare burden; as the infection can be recurrent, overall costs can accumulate. We undertook a systematic literature review (SLR) to examine the economic burden of illness for GC in key countries. Methods: Systematic searches were conducted in MEDLINE, EMBASE, and Cochrane databases to identify English-language articles published from January 1, 2009–December 1, 2019 reporting data on the economic burden of uncomplicated urogenital GC (uuGC) in the US, the UK, Germany, Japan and China. The SLR was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (2009). Articles were evaluated for eligibility using population, intervention, comparison, outcome, study design and time period criteria (Table). Dual-independent screening was used at both the abstract and full-text levels; data were captured by a single reviewer with validation by a second reviewer. Table. PICOS-T Study Selection Criteria Results: The SLR identified 27 eligible articles (Figure), of which 17 studies (16 US, 1 UK) reported the economic burden of uuGC. The studies primarily reported cost data, with a subset reporting limited resource use. Lifetime costs for uuGC, when elaborated upon, considered the potential for pelvic inflammatory disease among women, and epididymitis in men, as well as lifetime medical costs associated with human immunodeficiency virus. Among the 16 studies reporting costs, the total estimated lifetime cost of uuGC in the US reached as high as 162.1 million. Costs varied vastly based on sex, with one study reporting lifetime estimates up to 163, 433 for men but 7, 534, 692 for women in 2005. Nine studies described costs per patient/infection and found average costs ranging from 26.92–438.46, though most fell in the range of 79–354. Figure. PRISMA flow diagram of study inclusion and exclusion Conclusion: We identified a large body of evidence detailing the economic burden of GC. The cost burden varied by sex and was higher for females. However, the vast majority of the evidence came from the US, highlighting the need for more global research. Disclosures: Amber Martin, BS, Evidera (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder) Monica Turner, MPH, Evidera (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Emma Schiller, BA, Evidera (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder)